EKOLOGI DAN PATOGENITAS KUMAN LEPTOSPIRA - Tanzil, Kunadi (MAJALAH ILMIAH WIDYA, 2012)
Genus Leptospira is member of Leptospiraceae family with a tightly coiled, thin, flexible 5-15 Î¼m long, with very fine spirals 0,1-0,2 Î¼m wide; one end is often bent, forming a hook. Leptospirosis are essentially animal infections, human infection is only accidental,following contact with water or other materials contaminated with the excreta of animal hosts. The purpose of this paper is to explainthe causes of leptospirosis, ecology, pathogenesis clinical symptoms, diagnostic and to prevent the leptospirosis. The method is basedon literature study and other data. It is concluded that: (1) leptospirosis is a zootoxins disease caused by pathogenic leprosies andis characterized of clinical manifestation, varying from in apparent infection to fatal disease. (2) Diagnosis of leptospirosis can be doneby clinical presentation, isolating, and microscopic examination and serological examined from collection of the specimenspatient